Anti-Müllerian Hormone Level Decline in Patients Undergoing Hysterectomy With and Without Oophorectomy Compared With Natural Menopause. Issue 2 (4th February 2023) - Santoro, Nanette; Flyckt, Rebecca; Davis, Anne; Finkelstein, Joel; Crawford, Sybil; Sun, Fangbai; Derby, Carol; Morrison, Anthony; Sluss, Patrick; Zhang, Heping
Abstract : Anti-müllerian hormone levels decline similarly in patients who have hysterectomy with conservation of one or both ovaries when compared with patients undergoing natural menopause. Abstract : OBJECTIVE: To evaluate the relationship between hysterectomy with and without ovarian conservation and the onset of ovarian failure using anti-müllerian hormone (AMH) levels and imputed final menstrual period (FMP). METHODS: A total of 1, 428 women with an observed FMP and 232 women who underwent hysterectomy (159 with bilateral salpingo-oophorectomy [BSO], 13 with one ovary conserved, and 60 with both ovaries conserved) and who had serial AMH measurements were included from SWAN (The Study of Women's Health Across the Nation), a multi-ethnic, multi-site, community-based study. Anti-müllerian hormone levels were sampled annually with at least one presurgery or pre-FMP measurement at least one postsurgery or post-FMP measurement. Surgery-related differences in patterns of AMH levels with respect to surgery date or FMP were estimated using piecewise linear mixed modeling; differences in age at first undetectable AMH level were estimated using survival analyses. RESULTS: Patients with conservation of one or both ovaries or natural menopause demonstrated similar patterns of decline in AMH levels when anchored to surgery or FMP. Patients with hysterectomy (all types) had a later counterfactual FMP (52.9±0.2 SEM) compared with the observed FMP in those with natural menopause (52.1±0.1 years, P =.002). Those undergoing BSO had an immediate reduction in AMH level to undetectable after surgery. CONCLUSION: Hysterectomy does not lead to a more rapid decline in AMH levels postoperatively compared with natural menopause. Patients undergoing BSO have a rapid loss of AMH, consistent with complete removal of the ovaries. These data suggest that hysterectomy as currently performed does not compromise ovarian reserve.